2019
DOI: 10.3390/foods8120690
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Smoking Procedures on the Content of 16 PAHs in Traditional Dry Cured Smoked Meat “Hercegovačka Pečenica”

Abstract: During smoking, meat products may get contaminated by polycyclic aromatic hydrocarbons (PAH), especially the ones that are smoked in traditional (uncontrolled) conditions. This study aims to evaluate the difference in PAH content in samples of traditional dry cured pork meat products, "Hercegovačka pečenica", produced in (1) a traditional smokehouse and (2) in industrial chambers. The study revealed that the content of the four priority PAHs (PAH4) in samples produced in a traditional smoking manner highly exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…On the other hand, Mastanjević et al [17] reported significantly higher concentrations of PAHs in the dry-cured meat product Slavonska šunka. Also, Puljić et al [20] reported higher levels of PAHs in the traditionally smoked dry-cured meat product Hercegovačka pečenica. This can be explained by the different smoking procedures in the traditional production of these products such as combustion conditions (distance from the fire, wood type, or fire height).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Mastanjević et al [17] reported significantly higher concentrations of PAHs in the dry-cured meat product Slavonska šunka. Also, Puljić et al [20] reported higher levels of PAHs in the traditionally smoked dry-cured meat product Hercegovačka pečenica. This can be explained by the different smoking procedures in the traditional production of these products such as combustion conditions (distance from the fire, wood type, or fire height).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic separation of 16 PAHs of interest, was performed by gas chromatography in combination with a mass detector (GC-MS) according to Mastanjević et al [3] and Puljic et al [20]. In short, standard solutions of PAHs were prepared with a PAH mix of 16 polycyclic aromatic hydrocarbons 500 ± 0.2 µg/mL (Ultra Scientific, North Kingstown, RI, USA).…”
Section: Gc-ms (Gas Chromatography-mass Spectrometry) Analysismentioning
confidence: 99%
“…The contents of PAH in smoked fishes in the present study are very close to the mean concentration of 6PAHs (263 µg/kg) found in smoked and dried fishes exported in France by Togo and Ivory Coast (Hirsch, 2003).The results found in this study confirm Puljic & al(2019)works. They found the similar content of 4PAH in traditional smoked meat in the southern region of Bosnia and Herzegovina (Puljić et al, 2019). The samples of ADAW2 present a content of BaP (1.4µg/kg) lower than the BaP ML (5.0 μg/kg) and the sum of 4PaH (35μg/kg) is slightly higher than 4PAH ML (30,0 μg/kg).…”
Section: Assessment Of Lifetime Excess Cancer Risk Cr0 Of Pahs In Smomentioning
confidence: 89%
“…PAHs are organic compounds and have two or more fused aromatic rings and are known as a potential health hazard (Auby et al, 2013;Puljić et al, 2019).There are 16 PAHs identified by the U.S. Environmental Protection Agency (Nisbet et al, 1984). The seven (7) most important probably recognized as carcinogenic for humans are: benz[a]anthracene,(BaA), chrysene (CHR), benzo[b]fluoranthene (BbF), benzo[k]flouranthene (BkF), benzo[a]pyrene (BaP), indeno [1,2,3-cd]pyrene (IcP), dibenz[a,h]anthracene (DhA).Even thoughthey have natural and anthropogenic origin, PAHs can contaminate food in many ways throughpyrolysis and incomplete combustion of organic matter like wood during the process of smoking (Doornaert et al, 2003).…”
mentioning
confidence: 99%
“…Puljić et al [6] evaluated the differences in polyciclic aromatic hydrocarbons (PAHs) content in samples of traditional dry cured pork meat products made in Herzegovina, subjected to uncontrolled (traditional smokehouse) and industrial smoking processes. The results highlighted that the use of traditional smoking methods resulted in higher PAH contamination than the industrial one.…”
mentioning
confidence: 99%